Security in Wireless Sensor Networks - Oreku, George S.; Pazynyuk, Tamara (Risk Engineering,, 2016)
This monograph covers different aspects of sensor network security including new emerging technologies. The authors present a mathematical approach to the topic and give numerous practical examples as well as case studies to illustrate the theory. The target audience primarily comprises experts and practitioners in the field of sensor network security, but the book may also be beneficial for researchers in academia as well as for graduate students.